Greatness code : the formula behind unstoppable success - Guarino, Alan C. (John Wiley, 2026)
Unlock the qualities of success and reach your full potential using this effective guide from leadership and career development expert Alan C. Guarino. Your personal greatness objective is self-defined. For each of us, the definition of success and the journey to achieve it is different. Yet, no matter how talented or driven you are, your ability to achieve greatness is significantly influenced by many factors outside of your control. Leadership sets the tone--defining not just what they think success looks like, but also how you are expected to show up, collaborate, and grow. Greatness Code: The Formula Behind Unstoppable Success shows how to achieve your personal and career related goals. As Vice Chairman of Korn Ferry and the founder of Cornell International, Inc., Guarino devised a formula for success from thousands of data points over decades, helping people achieve their goals. Anyone who achieves their own greatness gets there by applying their social capital and building on five critical qualities: Persistence Stamina Courage Resilience Passion Your personally defined goal of greatness is achievable for almost anyone using this formula. In addition, Greatness Code provides scientific research and real-life examples that show how to advance at every career stage. It's time for you to gain the edge that these tools can give you. It's time to crack the Greatness Code.